2016
DOI: 10.5539/jas.v8n11p105
|View full text |Cite
|
Sign up to set email alerts
|

Mint Extract Present Antioxidant Action on the Erythrocytes of Dairy Cows Suffering from Mastitis?

Abstract: <p>Bovine Mastitis is an infection of the mammary glands that represents important economic losses in milk production. As in other pathologies, medicinal plants emerged as an important alternative for treatment of this condition. In this sense, the aim of this study was to investigate the antioxidant activity of the extract of <em>Mentha arvensis</em> L. on the erythrocytes of healthy dairy cows (P1); of dairy cows with mastitis without previous treatment (P2); and of dairy cows with mastitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This finding is not in line with the literature. One study [ 63 ] in dairy cows found no significant differences in the concentration of carbonylated proteins in healthy subjects and subjects with subclinical and clinical endometritis, and other studies conducted on dogs with systemic inflammatory response syndrome (SIRS) [ 40 , 41 , 64 ], horses with SIRS [ 38 ], calves parasitized by Theileria annulata [ 39 ], and cows with mastitis [ 42 , 43 ] demonstrated statistically increased PCC concentrations between the pathological subjects and healthy control groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is not in line with the literature. One study [ 63 ] in dairy cows found no significant differences in the concentration of carbonylated proteins in healthy subjects and subjects with subclinical and clinical endometritis, and other studies conducted on dogs with systemic inflammatory response syndrome (SIRS) [ 40 , 41 , 64 ], horses with SIRS [ 38 ], calves parasitized by Theileria annulata [ 39 ], and cows with mastitis [ 42 , 43 ] demonstrated statistically increased PCC concentrations between the pathological subjects and healthy control groups.…”
Section: Discussionmentioning
confidence: 99%
“…In veterinary medicine, there are a few studies about PCC that have shown an increased concentration of plasma PCC in horses with systemic inflammatory response syndrome [ 38 ], buffalos with Theileria annulata [ 39 ], and dogs with sepsis [ 40 , 41 ]. In bovine medicine, PCC concentration was evaluated in the milk of healthy animals and dairy cattle with mastitis [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%